2003
DOI: 10.1177/106286060301800203
|View full text |Cite
|
Sign up to set email alerts
|

Do Hospitals With Lower Mortality Have Higher Patient Satisfaction? A Regional Analysis of Patients With Medical Diagnoses

Abstract: Although patient satisfaction is a widely used indicator of quality, relationships between satisfaction and other indicators are poorly studied. The current study examined hospital-level correlations between patient satisfaction and severity-adjusted mortality for 29 hospitals in northeastern Ohio during 1993-1997. Satisfaction with 6 dimensions of care was measured using a validated survey of 42,255 randomly selected patients with medical diagnoses. Severity-adjusted mortality rates were determined for 200,56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…We also compared care satisfaction with wellestablished quality indicators that served as objective benchmarks. Finally, although studies have undertaken ecological analyses that have correlated institutional satisfaction ratings with severity-adjusted hospital mortality rates, 29 the present study is the first to explore the relationship between patient The reasons for the lack of a relationship between care quality and patient satisfaction observed in the present study are likely multifactorial but may be attributable to differences in treatment expectations between patients and healthcare providers. 30 A large study of Medicare beneficiaries found that patients in regions with higher levels of health spending for conditions including AMI did not report greater satisfaction with care.…”
Section: Discussionmentioning
confidence: 72%
“…We also compared care satisfaction with wellestablished quality indicators that served as objective benchmarks. Finally, although studies have undertaken ecological analyses that have correlated institutional satisfaction ratings with severity-adjusted hospital mortality rates, 29 the present study is the first to explore the relationship between patient The reasons for the lack of a relationship between care quality and patient satisfaction observed in the present study are likely multifactorial but may be attributable to differences in treatment expectations between patients and healthcare providers. 30 A large study of Medicare beneficiaries found that patients in regions with higher levels of health spending for conditions including AMI did not report greater satisfaction with care.…”
Section: Discussionmentioning
confidence: 72%
“…While a number of studies have suggested that there is an association between the hospital characteristics [such as administration, management, environment and settings] and patient's characteristics [demographic and socio-economic factors and health status], with the patient satisfaction [13,14,15], another strand of research has found that subjective experiences of received care and service and health status are stronger predictors of patient satisfaction compared to socio-demographic determinants [16,17,18]. The differences in the findings 142…”
Section: Introductionmentioning
confidence: 82%
“…In example, a number of studies have found a significant relationship between the patient's age and satisfaction [24; 25] in patient satisfaction tended to increase with age. Employment status is also a variable that has been found in some studies to have a significant relationship with patient satisfaction [26]. Interestingly, two study done in Germany indicated that patients perception of care are more important determinants of patient satisfaction compared to demographic characteristics of the patients and the characteristics of the visit [18; 27].…”
Section: Discussionmentioning
confidence: 99%
“…Physician and nursing services have been previously evaluated using this methodology. 13,21 As the profession moves forward with the transitions of care program, pharmacy struggles to find the optimal role for pharmacists, technicians, residents, and support staff around the transitional experience. 8,19,22 The importance of pharmacy services for medication reconciliation, discharge counseling, and follow-up during the transitions of care has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…11 Patient satisfaction was correlated with certain hospital conditions that are prevalent in institutions. 12 Jaipaul and colleagues 13 found that hospitals with higher patient satisfaction tended to have lower severity-adjusted mortality and fewer readmissions and hospital days. Patient satisfaction scores were also associated with lower readmission rates for heart failure and pneumonia patients.…”
Section: Mapmentioning
confidence: 99%